2018
DOI: 10.3389/fimmu.2018.01959
|View full text |Cite
|
Sign up to set email alerts
|

Mucosal Autoimmunity to Cell-Bound GP2 Isoforms Is a Sensitive Marker in PSC and Associated With the Clinical Phenotype

Abstract: Introduction: Zymogen granule glycoprotein 2 (GP2) was demonstrated as first autoimmune mucosal target in primary sclerosing cholangitis (PSC) associated with disease severity. Autoantibodies to four GP2 isoforms (aGP21−4) were found in patients with inflammatory bowel diseases but reactivity against specific GP2 epitopes has not been investigated in PSC yet. Hence, the prevalence of aGP21−4 and their association with the PSC phenotype for risk prediction were examined.Methods: GP2 isoforms were stably express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 48 publications
5
20
0
Order By: Relevance
“…Combined testing for IgA to GP2 isoforms 1 (large isoform) and 4 (small isoform) was superior to the analysis of autoAbs to just one GP2 isoform and resulted in a sensitivity of 66% in the 212 patients with PSC [104]. AutoAbs to GP2 isoforms 1 and 4 were independent risk predictors for the severity of disease (occurrence of cirrhosis) after adjusting for age and gender [104].…”
Section: Autoantigenic Targets In Psc-lessons From Humoral Autoimmunimentioning
confidence: 98%
See 2 more Smart Citations
“…Combined testing for IgA to GP2 isoforms 1 (large isoform) and 4 (small isoform) was superior to the analysis of autoAbs to just one GP2 isoform and resulted in a sensitivity of 66% in the 212 patients with PSC [104]. AutoAbs to GP2 isoforms 1 and 4 were independent risk predictors for the severity of disease (occurrence of cirrhosis) after adjusting for age and gender [104].…”
Section: Autoantigenic Targets In Psc-lessons From Humoral Autoimmunimentioning
confidence: 98%
“…These GP2 isoforms encompass two larger and two smaller isoforms whereby the large and small isoforms differ in only three amino acids (valine-proline-arginine) [64]. Intriguingly, autoAbs to all four GP2 isoforms, which were expressed as glycosylphosphatidylinositol (GPI)-anchored membrane molecules in a human cell line, could be determined by IFA in patients with PSC from four European university hospitals [104]. Combined testing for IgA to GP2 isoforms 1 (large isoform) and 4 (small isoform) was superior to the analysis of autoAbs to just one GP2 isoform and resulted in a sensitivity of 66% in the 212 patients with PSC [104].…”
Section: Autoantigenic Targets In Psc-lessons From Humoral Autoimmunimentioning
confidence: 99%
See 1 more Smart Citation
“…These isoforms differ by 3 amino acids (valine-proline-arginine) 30 and were previously described in PSC. 23 All assays were carried out according to the manufacturer's instruc-…”
Section: Autoantibodiesmentioning
confidence: 99%
“…Other studies identified IgA against the pancreatic major zymogen granule glycoprotein 2 (GP2) as a marker of disease severity in PSC. [21][22][23][24] Anti-GP2 antibodies (anti-GP2) are members of the family of pancreatic autoantibodies directed against proteins predominantly expressed in the exocrine pancreas. 25 In total, four human GP2 isoforms (GP2 1−4 ) were identified and both IgA, as well as IgG autoantibodies were detected in humans.…”
Section: Introductionmentioning
confidence: 99%